PHYSICO-CHEMICAL INTERACTIONS BETWEEN COMPONENTS OF THE Al/SiO2 SYSTEM IN METALLURGICAL SYNTHETIC PROCESSES OF CASTING PARTICULATE REINFORCED ALUMINUM ALLOYS - I. V. Rafalski; B. M. Nemenenok (Литьë и металлургия, 2017)
The physicochemical interactions between components in the Al/SiO2 aluminum matrix compositions under various temperature conditions of processing are studied. The synthesis of aluminum oxide ceramics in aluminum melts for the production of particulate reinforced Al-Si/Al2O3 alloys was performed. The addition of dispersed particles of silicon oxide ceramics was carried out by mixing into aluminum melt in a liquid-solid state. At the temperature-time processing of the Al/SiO2 compositions, alumina ceramic with a contact surface layer providing spontaneous wetting with liquid aluminum is realized.